1998
DOI: 10.1038/sj.ejhg.5200194
|View full text |Cite
|
Sign up to set email alerts
|

Absence of homozygosity for predominant mutations in PMM2 in Danish patients with carbohydrate-deficient glycoprotein syndrome type 1

Abstract: Carbohydrate-deficient glycoprotein syndrome type 1 (CDG1; McKusick No. 212065) is an autosomal recessively inherited disease characterised clinically by central nervous system dysfunction and biochemically by hypoglycosylation of many serum proteins. Most patients with CDG1 have deficient activity of phosphomannomutase. The locus for this enzyme has been mapped to 16p13, and a gene, PMM2, encoding phosphomannomutase has been isolated. We identified 34 mutations on 36 disease chromosomes in 18 unrelated Danish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
3
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 12 publications
(30 reference statements)
3
62
3
2
Order By: Relevance
“…Figure 3 shows the activities expressed as percent of normal wild type human PMM activity. The plasmid carrying the common mutation R141H 40,41 gave the same activity as the vector without insert. This finding is expected, because this mutation is believed to be lethal in the homozygous state.…”
Section: Mutations In Pmm2 and Their Consequencesmentioning
confidence: 68%
“…Figure 3 shows the activities expressed as percent of normal wild type human PMM activity. The plasmid carrying the common mutation R141H 40,41 gave the same activity as the vector without insert. This finding is expected, because this mutation is believed to be lethal in the homozygous state.…”
Section: Mutations In Pmm2 and Their Consequencesmentioning
confidence: 68%
“…4,8 The most intriguing observation is the total lack of patients homozygous for the most frequent mutation, R141H, present in more than 75% of patients of Caucasian origin. 4,5 On the other hand, patients homozygous for the other relatively frequent mutation, F119L, have been found, 4,6,9 (see also M Schwartz 1999, unpublished data) as well as one patient homozygous for the rare D65Y mutation. 4 These observations suggested that the R141H mutation is a severe mutation, and that homozygosity may not be compatible with life.…”
Section: Introductionmentioning
confidence: 99%
“…3 In two independent surveys on patients with CDG-Ia, mutations in the coding region of the PMM2 gene were found on 145 of 148 disease chromosomes (98%). [3][4][5] The majority of the 30 different mutations detected so far have been of the missense type. [3][4][5][6][7] Probably, only such mutations that retain residual enzymatic activity are tolerated in patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No patient homozygous for this mutation has been reported, because this severe mutation is not compatible with life in the homozygous state. [3][4][5] The standard reference sequence indicating reported variants (ENSG00000140650) and a reference for exon numbering (ENST00000268261) can be found at www.ensemble.org.…”
Section: Mutational Spectrummentioning
confidence: 99%